2008
DOI: 10.1088/1674-1056/17/7/049
|View full text |Cite
|
Sign up to set email alerts
|

High density gas state at water/graphite interface studied by molecular dynamics simulation

Abstract: In this paper molecular dynamics simulations are performed to study the accumulation behaviour of N2 and H2 at water/graphite interface under ambient temperature and pressure. It finds that both N2 and H2 molecules can accumulate at the interface and form one of two states according to the ratio of gas molecules number to square of graphite surface from our simulation results: gas films (pancake-like) for a larger ratio and nanobubbles for a smaller ratio. In addition, we discuss the stabilities of nanobubbles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…18 More difficult is the comparison with computational results available in the literature, which also predicts a large oversaturation at the solidliquid interfaces. 17,41 In fact, in these works, the authors use a different computational approach consisting of preparing a sample with a very high gas oversaturation and determining the gas local oversaturation profile as a function of the distance from the surface. In our case, in constrast, thanks to the use of RMD to compute the free energy, we can consider more realistic bulk oversaturation conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 More difficult is the comparison with computational results available in the literature, which also predicts a large oversaturation at the solidliquid interfaces. 17,41 In fact, in these works, the authors use a different computational approach consisting of preparing a sample with a very high gas oversaturation and determining the gas local oversaturation profile as a function of the distance from the surface. In our case, in constrast, thanks to the use of RMD to compute the free energy, we can consider more realistic bulk oversaturation conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a local oversaturation in this region can effectively counteract the gas outflux. A number of recent experiments have shown that, indeed, one can produce a large local gas oversaturation at the solid/water interface 17,18 and when the oversaturation reaches a critical value, of the order of ζ ∼150-250, nanobubbles are formed. [19][20][21] Among the others, Zhou et al have performed near-edge X-ray absorption fine structure experiments showing a large gas oversaturation in the liquid surrounding nanobubbles.…”
Section: Introductionmentioning
confidence: 99%
“…Many mechanisms have been proposed for surface nanobubble stability, but so far a complete molecular explanation for experimental observations is lacking. Some proposed necessary mechanisms include experimental contamination, dynamic equilibrium of fast-flowing gas streams, interfacial gas enrichment (IGE), pinning to surface heterogeneities, , and gas oversaturation. , From the view point of interfacial effects, explanations for surface nanobubble stability follow two main categories: (1) those that involve substrate effects near the fluid–solid interfaces and (2) those that focus on molecular interactions at the gas–water interface. The first category proposes that gas enrichment occurs along the hydrophobic substrate surface because of gas molecule aggregation in the water-depleted region near the hydrophobic surface. This is supported by all-atom molecular dynamics (MD) simulations finding high-density gas adjacent to the substrate surface , and a growing body of empirical evidence for the coexistence of nanobubbles and IGE layers. ,, Another critical mechanism in this category involves contact line pinning stabilization, which is supported by a few experimental observation and theoretical estimates. , …”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] A molecular dynamics study revealed that nanobubbles appear in the form of the high density gas state at the water-graphite interface. 10 Recently, nanobubbles with a few hundred nanometres diameter were detected in bulk water by dynamic light scattering. 11,12 The major issue to be understood is the stability of nanobubbles in water.…”
mentioning
confidence: 99%